Temporal Trends in Fertility Rates: A Nationwide Registry Based Study from 1901 to 2014. - Martin Blomberg Jensen; Lærke Priskorn; Tina Kold Jensen; Anders Juul; Niels Erik Skakkebaek (PLoS ONE, 2015)
Increasing age at first childbirth has been suggested to increase the risk for infertility. Our objective is to determine whether women above thirty years of age historically have been able to sustain fertility rates above replacement level.A descriptive nationwide Danish study using birth registries from 1901-2014.Information on women's age at childbirth was obtained by using records from primary, secondary and tertiary institutions.Mothers to 8,024,969 live births.Mothers were stratified according to age at childbirth to determine total and age specific fertility rates.Total fertility rate (TFR) decreased from 4.1 to 1.8 children per woman and age specific fertility also decreased from 1901 to 2014. Women aged 30-34, 35-39 or 40-44 years in the first decade of the 20th century had higher fertility rates than the corresponding five year younger age groups (25-29, 30-34 and 35-39, respectively) have had for the last 65 years. On average, women gave birth to two children after the age of 30 and one or more child after 35 years of age in the beginning of the 1900s. Furthermore, women more than 40 years of age accounted for 10% of TFR in 1901 compared with 4% in 2014 despite usage of assisted reproduction.This nationwide study shows that women above 30 years of age historically have been able to sustain fertility rates above replacement level. This implies that other factors besides age are strong determinants of fertility in women above 30 years of age.